1973
DOI: 10.3758/bf03333363
|View full text |Cite
|
Sign up to set email alerts
|

Aging adults and rate of memory scan

Abstract: Adults 20-25, 35-40, and 50-55 years old were examined on Sternberg's paradigm for rate of memory search. There were no differences between the two younger age groups in either overall performance or rate of memory scan, but the 50-55 year olds required approximately 50% more time per memory comparison than the two younger groups. Also, their intercepts were significantly greater.The effects of advancing age in humans are easy to chronicle at the physiological level, but they are less readily characterized or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0

Year Published

1975
1975
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 1 publication
(1 reference statement)
4
24
0
Order By: Relevance
“…Working memory shows a downward trajectory across the adult lifespan in non-demented individuals (Park et al, 2002) with deficits often observed in paradigms that manipulate memory load (Anders et al, 1972; De Beni and Palladino, 2004; Eriksen et al, 1973; Orsini et al, 1987) and demands on the attention and executive systems (Holtzer et al, 2004; 2005). The latter findings are consistent with the premise that working memory depends on attention resources (Kane et al, 2001; Engle et al, 1999b) that decline with age (Craik, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Working memory shows a downward trajectory across the adult lifespan in non-demented individuals (Park et al, 2002) with deficits often observed in paradigms that manipulate memory load (Anders et al, 1972; De Beni and Palladino, 2004; Eriksen et al, 1973; Orsini et al, 1987) and demands on the attention and executive systems (Holtzer et al, 2004; 2005). The latter findings are consistent with the premise that working memory depends on attention resources (Kane et al, 2001; Engle et al, 1999b) that decline with age (Craik, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…The rate of change of the curve's slope represents the rate at which information becomes available for decision making. In these ways, the x-intercept and rate parameters describe how efficiently WM retrieves information, and the asymptote parameter describes WM capacity.Aging is known to impair the speed of encoding new information in WM (Salthouse, 1992;Salthouse & Babcock, 1991), and older adults have longer reaction times than young adults in delayed item recognition (Anders et al, 1972;Eriksen, Hamlin, & Daye, 1973;Holtzer et al, 2004;Zarahn, Rakitin, Abela, Flynn, & Stern, 2007). We therefore predicted a more acute tradeoff for older adults than for young adults.…”
mentioning
confidence: 95%
“…The significance of Sternberg's degradation finding to the study of aging is the similarity between the typical finding of an increased slope and intercept of the older adult's RT function (Anders & Fozard, 1973;Anders, Fozard, & Lillyquist, 1972;Eriksen, Hamlin, & Daye, 1973;Madden & Nebes, 1980;Salthouse & Somberg, 1982) and the results of Sternberg's young adults' performance under degraded conditions in the first session of testing. It may be that reductions in encoding efficiency may affect the efficiency of the older adult's comparison process.…”
Section: Stimulus Integrity and Letter Matching 157mentioning
confidence: 73%